Systematic Literature Review : E-LKPD Berbasis STEM-E Materi Sistem Persamaan Linear Dua Variabel - Revita, Ade Nindya; Refianti, Rani; Nugroho, Khathibul Umam Zaid (Papanda, 2025)
This study aims to conduct a Literature review study on STEM Education-based E-LKPD on the material of two-variable linear equation systems and identify and conclude the findings of existing research. The method used is a Systematic Literature Review using 13 relevant articles from accredited national journals collected through Google Scholar. The development of STEM Education-based E-LKPD has demonstrated critical thinking skills in Literature Review. The stages in this Systematic Literature Review process are Planning, Conducting, and Reporting. Data were collected by reviewing or reading every article about STEM Education-based E-LKPD on SPLDV material published from 2015-2024. The results of the study show that this E-LKPD is able to increase active student participation, facilitate conceptual understanding, and strengthen mathematical problem-solving abilities. This media is also considered effective in supporting independent and interactive learning, so that it is in line with the goal of improving the quality of mathematics learning.